Efficient Reduction of CO2 into Formic Acid on a Lead or Tin Electrode using an Ionic Liquid Catholyte Mixture. Issue 31 (17th June 2016) - Zhu, Qinggong; Ma, Jun; Kang, Xinchen; Sun, Xiaofu; Liu, Huizhen; Hu, Jiayin; Liu, Zhimin; Han, Buxing
Abstract: Highly efficient electrochemical reduction of CO2 into value‐added chemicals using cheap and easily prepared electrodes is environmentally and economically compelling. The first work on the electrocatalytic reduction of CO2 in ternary electrolytes containing ionic liquid, organic solvent, and H2 O is described. Addition of a small amount of H2 O to an ionic liquid/acetonitrile electrolyte mixture significantly enhanced the efficiency of the electrochemical reduction of CO2 into formic acid (HCOOH) on a Pb or Sn electrode, and the efficiency was extremely high using an ionic liquid/acetonitrile/H2 O ternary mixture. The partial current density for HCOOH reached 37.6 mA cm −2 at a Faradaic efficiency of 91.6 %, which is much higher than all values reported to date for this reaction, including those using homogeneous and noble metal electrocatalysts. The reasons for such high efficiency were investigated using controlled experiments. Abstract : Just a splash : Addition of a small amount of water to an ionic liquid/acetonitrile electrolyte mixture enhanced the efficiency of the electrochemical reduction of CO2 into formic acid significantly using a Pb or Sn electrode. The partial current density for HCOOH was as high as 37.6 mA cm −2 at a Faradaic efficiency of 91.6 %.